Inner Kinetochore Protein Interactions with Regional Centromeres of Fission Yeast - Thakur, Jitendra (Genetics, 2015)
Centromeres of the fission yeast Schizosaccharomyces pombe lack the highly repetitive sequences that make most other "regional" centromeres refractory to analysis. To map fission yeast centromeres, we applied H4S47C-anchored cleavage mapping and native and cross-linked chromatin immunoprecipitation with paired-end sequencing. H3 nucleosomes are nearly absent from the central domain, which is occupied by centromere-specific H3 (cenH3 or CENP-A) nucleosomes with two H4s per particle that are mostly unpositioned and are more widely spaced than nucleosomes elsewhere. Inner kinetochore proteins CENP-A, CENP-C, CENP-T, CENP-I, and Scm3 are highly enriched throughout the central domain except at tRNA genes, with no evidence for preferred kinetochore assembly sites. These proteins are weakly enriched and less stably incorporated in H3-rich heterochromatin. CENP-A nucleosomes protect less DNA from nuclease digestion than H3 nucleosomes, while CENP-T protects a range of fragment sizes. Our results suggest that CENP-T particles occupy linkers between CENP-A nucleosomes and that classical regional centromeres differ from other centromeres by the absence of CENP-A nucleosome positioning.